Constructing synergistically strengthening-toughening 3D network bundle structures by stereocomplex crystals for manufacturing high-performance thermoplastic polyurethane nanofibers reinforced poly(lactic acid) composites. (8th February 2023) - He, Yue; Jia, Shun-Heng; Fang, Cong; Tan, Ling-Cao; Qin, Sen; Yin, Xiao-Chun; Park, Chul B.; Qu, Jin-Ping
Abstract: As one of the most promising biodegradable materials, poly(lactic acid) (PLA) is seriously restricted by its notorious inherent brittleness and weak heat distortion resistance. In this work, a novel and simple methodology is proposed using an eccentric rotor extruder (ERE) with a predominantly elongational flow field to manufacture high-performance engineered poly(L-lactic acid)/poly(D-lactic acid)/thermoplastic polyurethane nanofiber composites on an industrial scale. The oriented tough TPU nanofibers (TNFs), rigid integrated PLA hybrid crystals and their good interface compatibility produce a strengthening-toughening bundle structure. When the PDLA content reached 3 wt%, the bundle structures interlinked with each other to form a strengthening-toughening 3D network. This resulted in a high-performance engineered 80L/5D/15T nanofiber composite with super toughness of 74.1 kJ/m 2, high strength of 47.3 MPa and superior Young's modulus of 1378 MPa, which are 28.6 times, 85% and 92.7%, respectively, compared with neat PLLA. Compared with those published literatures, the 80L/5D/15T nanofiber composite not only possesses super toughness (more than 28 times) but also maintains good strength (maintain 85%), additionally good heat distortion resistance was also obtained. The performance of 80L/5D/15T nanofiber composite was significantly superior in comparison with biodegradable plastics as well as petroleum-based non-degradable general-purpose plastics and engineering plastics, demonstrating its enormous potential as a substitute structural material in harsh environments. It is believed that the novel and industrial scale methodology opens new perspectives for manufacturing other high-performance engineered biodegradable materials. Graphical abstract: Image 1